2017
DOI: 10.1159/000485008
|View full text |Cite
|
Sign up to set email alerts
|

Roscovitine, a CDK5 Inhibitor, Alleviates Sevoflurane-Induced Cognitive Dysfunction via Regulation Tau/GSK3β and ERK/PPARγ/CREB Signaling

Abstract: Background/Aims: Multiple exposures to anesthesia in children may increase the risk of developing cognitive impairment. Sevoflurane is an anesthetic that is commonly used in children during surgery. Cyclin-dependent kinase (CDK) 5 is involved in the regulation of sevoflurane-induced cognitive dysfunction, but the mechanistic details remain unclear. The present study evaluated the mechanism by which CDK5 mediates sevoflurane-induced cognitive dysfunction in mice. Methods: Hippocampal neurons were isolated from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
20
0
1

Year Published

2019
2019
2025
2025

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(21 citation statements)
references
References 28 publications
0
20
0
1
Order By: Relevance
“…For example, downregulation of GFAP expression by PPARγ depends on cyclin‐dependent kinase 5 (CDK5)‐evoked phosphorylation of PPARγ at serine 112. Moreover, activation of CDK5 increases glycogen synthase kinase‐3β and suppresses the activity of extracellular signal‐regulated protein kinase (ERK) 1/2/cyclic AMP response element‐binding protein signaling following sevoflurane exposure (Liu et al, ). Since glycogen synthase kinase‐3β is a cell apoptosis signal (Wang et al, ) and phosphorylated ERK 1/2 (pERK1/2) is a mitogenic kinase, changes in their activities by CDK5 can reduce astrocytic differentiation and GFAP expression (Hilliard et al, ).…”
Section: Expression Of Gfap and Its Regulationmentioning
confidence: 99%
“…For example, downregulation of GFAP expression by PPARγ depends on cyclin‐dependent kinase 5 (CDK5)‐evoked phosphorylation of PPARγ at serine 112. Moreover, activation of CDK5 increases glycogen synthase kinase‐3β and suppresses the activity of extracellular signal‐regulated protein kinase (ERK) 1/2/cyclic AMP response element‐binding protein signaling following sevoflurane exposure (Liu et al, ). Since glycogen synthase kinase‐3β is a cell apoptosis signal (Wang et al, ) and phosphorylated ERK 1/2 (pERK1/2) is a mitogenic kinase, changes in their activities by CDK5 can reduce astrocytic differentiation and GFAP expression (Hilliard et al, ).…”
Section: Expression Of Gfap and Its Regulationmentioning
confidence: 99%
“…Emerging evidence shows that SEV impairs memory consolidation in rats, possibly through inhibiting phosphorylation of GSK‐3β in the hippocampus . Also, our previous study already showed that SEV anesthesia caused alterations in apoptosis‐related proteins and GSK‐3β phosphorylation, and induced cognitive dysfunction in mice . In addition, it is reported that lithium treatment prevents apoptosis in neonatal rat hippocampus resulting from SEV exposure .…”
mentioning
confidence: 92%
“…Roscovitine reduced basal phosphorylation at AT8 (pSer202/pThr205) but did not affect the OA-induced tau hyperphosphorylation, reflecting its specificity and the selectivity to our cell models. Similarly, several recent studies revealed that inhibiting CDK5 with Roscovitine had neuroprotective properties against neurodegenerative conditions caused by decreasing tau phosphorylation (66, 76, 96). Like LiCl, Roscovitine resulted in opposite effects in the N2a cells by increasing phosphorylation at CP13 (pSer202) and PHF-1 (pSer396/pSer404).…”
Section: Discussionmentioning
confidence: 88%